1948
DOI: 10.1071/bi9480065
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Colour on the Numbers of Housefliesresting on Painted Surfaces

Abstract: SummaryA simple technique for determining the preference of houseflies for surfdces of various colours is described. This consists of liberating adults into a Peet·Grady testing chamher fitted with movable coloured corners. The numbers of flies rest· ing on the coloured corners are recorded at intervals to provide adequate data for comparison.The ascending order of preference for the particular colours lested was white and sky hlue (equal) ,light grey, green, yellow and medium grey (equal), dusky hIue, and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Mitchell et al (1975) also found no color to be more attractive than another; they used pie pan traps baited with trichlorfon and dichlorvos combined with sugar and treated with muscalure. This supports Waterhouse's (1947) conclusion that olfactory responses are stronger than visual cues for house fly orientation. Hecht (1970) concluded that the color itself may not be as important as the contrast of the color with the surrounding environment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Mitchell et al (1975) also found no color to be more attractive than another; they used pie pan traps baited with trichlorfon and dichlorvos combined with sugar and treated with muscalure. This supports Waterhouse's (1947) conclusion that olfactory responses are stronger than visual cues for house fly orientation. Hecht (1970) concluded that the color itself may not be as important as the contrast of the color with the surrounding environment.…”
Section: Discussionsupporting
confidence: 87%
“…Freeborn and Berry (1935) counted fly specks on a plywood board painted with various colors and placed in a dairy barn. Waterhouse (1947) observed the numbers and duration of flies resting on colored plywood sur-\ ,,) ,…”
mentioning
confidence: 99%
“…The decreased attractiveness of black in the swamp forest supports the idea that black represents deep shade for species of the G. palpalis group, but it is surprising that black is more attractive for females in the cool rainy season than in the dry season. Similar differences in responses to black and white also occur between different species of Musca (Waterhouse, 1948;Peterson & Meyer, 1978).…”
Section: Discussionmentioning
confidence: 52%
“…Flies other than D. repleta such as Musca domestica L. (Diptera: Muscidae) and Rhagoletis pomonella (Walsh) (Diptera: Tephritidae) are attracted to red and often to black (Waterhouse 1948;Pospisil 1962;Prokopy 1968). However, some of these attractions were not based on color, but on the contrast of the "colored" object with its surrounding environment (Prokopy 1968;Howard & Wall 1998).…”
Section: Discussionmentioning
confidence: 99%